Perineal Influence Massage and warm compresses during the active phase of labor for perineal tearing in PMB Dewi - Masruhah Erwina (Journal for Research in Public Health, 2022)
Background: High maternal mortality rate due to bleeding, one of which is due to a tear in the birth canal, around 4-5%. The percentage of perineal tears is small but this problem can be a serious problem in maternal deaths. The purpose of writing this research is to determine the influence of the perineum massage and warm compresses in the active phase of labor against perineal tears. Method: This type of research is quantitative, with research design included in the type of research experiment. In this research, a comparative quantitative research design will be used. Based on the research location, it is clinical research and there are treatments in the research. Based on the data source, it is primary research. This research is included in this type of research Almost Experimental with Posttest Only Control Group Design. In this research design, there are two groups selected randomly. One group acts as the control group and the other group acts as the experimental group. Then, within a predetermined time period, the experimental group was given treatment. Then measurements were carried out on both groups. This research was conducted at the Mandiri Dewi Midwife Practice, Sidoarjo. Results: The research results show that the distribution of events is not rupture perineum occurred more frequently in the intervention group of 6 people (85.7%) who received perineal massage and warm compresses. After testing Chi-Square earned value p= 0.005 (<0.05) then statistically it shows the influence of the perineum massage and warm compresses in the active phase of labor against perineal tears. Conclusion: There is Perineal Influence Massage and Warm Compresses in the Active Phase of Labor on the Incident of Perineal Tears in PMB Dewi. The secretion of the hormones progesterone and relaxin during pregnancy will increase; these hormones help muscles and joints to soften and stretch; This process takes place throughout the body, pelvic floor, and perineum. Slow, gentle perineal massage and warm compresses can increase the flexibility of the perineum as blood circulation increases. (Akhlaghi et al., 2019)